The Effects of an eight week plyometric-based program on motor performance skills and muscular power in 7-8-year-old primary school students - Sortwell, A.; Newton, M.; Marinho, D. A.; Ferraz, R.; Perlman, D. (International Journal of Kinesiology & Sports Science, 2021)
Background of Study: Competence in motor performance skills is important in enabling children to be physically literate. Plyometric-based training has been suggested as an effective means to enhance motor performance skills in young athletes. However, no studies have reported the effects of a whole body plyometric-based program integrated into physical education on motor performance skills with young children. Objective: This study aims to examine the effect of a plyometric-based program on primary school students` motor performance skills, upper and lower body muscular power, and reactive strength index. Method: The sample was composed of 61 primary school students, 29 girls and 32 boys, aged 7-8 years old, from two second-grade Physical Education (PE) classes. Both groups participated in their regular eight-week PE lessons (50-minute classes twice a week). During the study, the plyometric group performed a plyometric-based program in the 15-minute warmup of each class, while the comparison group performed regular warmup activities. Student`s motor performance skill proficiency, reactive strength index, lower and upper body muscular power were assessed before and after the eight weeks of PE lessons. The data were analysed using a two-way analysis of variance, followed by pairwise comparisons with the Bonferroni adjustment. Results: The data analysis indicated significant increases in motor performance skill proficiency, upper and lower body muscular power in the plyometric group vs comparison group (p = 0.05). Conclusion: These results suggest that including a plyometric-based program in the PE warmup phase of the lessons may improve motor performance skills and muscular power in primary school students.